The Up-to-Dateness of the Debate on Responsibility to Protect - Zajadło-Węglarz, Paulina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The aim of the article is to review the contemporary debate on the concept of Respon-sibility to Protect. Numerous publications concerning R2P are the best illustration of the fact that it is a very topical subject. Analysing the doctrinal issues focusing on new challenges for contemporary international law the author focuse on a visible change in the international law paradigm, transformation of moral norm into legal one and the effective use of the instruments of R2P application.